Transformando a bomolochía: o prazer da ficção nas histórias verdadeiras (Nuntius Antiquus, 2013)
The aim of this paper is to discuss Lucian’s statement that his novel Verae Historiae provides both pleasure (ψυχαγωγία) and θεωρία to the readers. I suggest that Lucian addresses the question of the production of fiction narratives in prose and how they should be read while arguing that his work is an appropriate reading to the pepaideuménoi.